Proposed new design scheme for MAS Golden Holiday Travel Agency at Lot 24 & 10 KL Sentral, Jalan Bangsar, 50450 Kuala Lumpur / Ahmad Hussaini Rosli - Rosli, Ahmad Hussaini (Faculty of Architecture, Planning and Surveying, 2005)
The purpose of this final project is to realise the design process that involve in the preliminary findings, analysis case study and synthesizing. The suggested title of this project is Proposed New Design Scheme For MAS Golden Holiday at unit 24 & 10, KL Sentral, Kuala Lumpur. Before writing this documentation, a lot of procedures has to be met and must follow a systematic process. Various important factors must be considered especially inside the angular space including environment outside the building. The first step is to identify constraints and limitations of the existing site, interior and exterior spaces. This is important as to identify the problem solving of the project. The research begins from basic design principles up to the building roof. Besides that, the research of interior space must also be considered as a case study. The nature of the case study directly or indirectly related to the project that I have proposed. In fact, a planning proposal was made before I started to do a new design. Several important aspects must be considered to ensure the space function, such as to fulfill user’s needs and comfort. The design made should fulfill the character of users or visitors demand and also match the concepts that need to be shown. By proposed this travel agencies, it is hoped that it will be able to give benefits to the tourist, our people and country.